Income and Employment Pattern of MNREGA Programme in District Sant Kabir Nagar: A Recent Study - Verma, Ambrish Kumar; Yadav, Bhartendu; Sachan, Anil; ., Akash (New Innovations in Economics, Business and Management Vol. 4, 2022)
The study was conducted using purposive cum random sampling procedure and seventy-five respondents were selected from a block of district. The data collected through personal interview method were classified, tabulated and analysed in the light of objectives of the study. MGNREGA is a beneficiary scheme, improving socioeconomic face of the maximum rural households in the research area selected. Most remarkable feature of MNREGA is that it pays women the same as men, something that was virtually unimaginable in rural India. It is seen that majority of the respondents are enjoying the income and employment rewards from the scheme and are further seeking it in the future. The wages provided and works assigned are found satisfactory to the households and MGNREGA is enhancing livelihood security in the study area.